2015
DOI: 10.1016/j.gecco.2014.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Deterring poaching in western Tanzania: The presence of wildlife researchers

Abstract: a b s t r a c tIllegal poaching threatens wildlife across Africa. Historically and even today, conservationists have lobbied local and national governments to create and better manage protected lands to reduce this threat. In many cases, however, governments are either unable or unwilling to invest further resources in exclusive protected areas, such as national parks. In addition to traditional methods, or where such approaches are not feasible, a complimentary form of protection is researcher presence, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 54 publications
0
53
0
Order By: Relevance
“…Evidence-based evaluation is required (Sutherland et al, 2004;Ferraro & Patanayak, 2006;Laurance, 2013) to support previous suggestions that researcher presence can have a positive effect on the protection of faunal communities (Köndgen et al, 2008;Tranquilli et al, 2012;Piel et al, 2015), as well as to understand the impacts of such benefits. In this study, we found differences in the abundance of chimpanzee and gorilla nests, the availability of suitable nesting habitat and the levels of human activity features in each site.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Evidence-based evaluation is required (Sutherland et al, 2004;Ferraro & Patanayak, 2006;Laurance, 2013) to support previous suggestions that researcher presence can have a positive effect on the protection of faunal communities (Köndgen et al, 2008;Tranquilli et al, 2012;Piel et al, 2015), as well as to understand the impacts of such benefits. In this study, we found differences in the abundance of chimpanzee and gorilla nests, the availability of suitable nesting habitat and the levels of human activity features in each site.…”
Section: Discussionmentioning
confidence: 98%
“…There is some evidence that researchers provide both active and passive protective effects, for example, by deterring poaching (Piel et al, 2015) or by offering financial benefits to adjacent communities who in turn will support protected areas (PAs; Laurance, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have documented the impact of habitat loss [2][3][4], poaching [5][6][7] and infectious disease [8,9] on wild populations. In Tanzania, 75% woodland vegetation than the closed riverine forest.…”
Section: Introductionmentioning
confidence: 99%
“…In the Issa valley, Tanzania, ten custom built solar powered acoustic transmission units (SPATUs) were deployed (Table 1) where the Ugalla Primate Project, a long-term research project, has been consistently running since 2008 [40]. The vegetation at Issa is predominantly miombo-woodland with interspersed grasslands, swamp, and riverine closed-canopy forest.…”
Section: Methodsmentioning
confidence: 99%